1997
DOI: 10.1063/1.872191
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic growth in the linear Richtmyer–Meshkov instability

Abstract: An analytic model for the asymptotic growth in the linear Richtmyer-Meshkov instability is presented. Analytic formulae for the interface velocity are obtained both in the weak and the strong shock limits, whether a shock or a rarefaction are reflected. For weak shocks, the irrotational approximation is used. For strong shocks, the vorticity in the bulk must be also taken into account. It is seen that this bulk vorticity actually lowers the velocity predicted by the irrotational approximation. An explicit appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
139
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(141 citation statements)
references
References 9 publications
2
139
0
Order By: Relevance
“…This process of velocity variation at the interface owing to the sound wave field occurs at any shock intensity (weak or strong shocks). Additionally, as the shocks separate from the contact surface, their oscillations will induce the generation of vorticity in the bulk (Kevlahan 1997;Wouchuk & Nishihara 1997;Wouchuk 2001a). This bulk vorticity is negligible compared with the interface circulation for weak shocks and/or very incompressible fluids.…”
Section: (B) Generation Of Vorticity By the Corrugated Shock Frontsmentioning
confidence: 99%
See 2 more Smart Citations
“…This process of velocity variation at the interface owing to the sound wave field occurs at any shock intensity (weak or strong shocks). Additionally, as the shocks separate from the contact surface, their oscillations will induce the generation of vorticity in the bulk (Kevlahan 1997;Wouchuk & Nishihara 1997;Wouchuk 2001a). This bulk vorticity is negligible compared with the interface circulation for weak shocks and/or very incompressible fluids.…”
Section: (B) Generation Of Vorticity By the Corrugated Shock Frontsmentioning
confidence: 99%
“…Incidentally, after some algebra, it can be shown that the quantities F m can also be written as weighted spatial averages of the vorticity profiles generated by each corrugated shock in the corresponding fluid, i.e. it can be seen that (Wouchuk & Nishihara 1997;Wouchuk 2001a)…”
Section: (B) Generation Of Vorticity By the Corrugated Shock Frontsmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer readers to the original sources of these more complex models. [13][14][15][16][17] B. Start-up time Lombardini 12 has developed a modified impulsive model that takes into account the affect of a reflected and transmitted shock on the instability start-up phase.…”
Section: E Boundary Conditionsmentioning
confidence: 99%
“…A great deal of research has been performed on Richtmyer-Meshkov instability since its introduction. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] A common component of most previously performed experimental and computational work has been the use of gases at conditions close to room temperature and pressure. In light of this, the current investigation is focused on exploring the role of the equation of state in RichtmyerMeshkov instability specifically in relation to commonly studied perfect gas cases.…”
Section: Introductionmentioning
confidence: 99%